Changes of grain production potential in farming–pastoral ecotone: a case study in West Jilin, China. (3rd April 2018) - Li, Fei; Zhang, Shuwen; Zhang, Yijing; Yang, Haijuan; Yang, Jiuchun
Abstract: Grain production potential is mainly influenced by agroclimate and land use. In the present study, substantial regional differences associated with the impact of climate change were found (i.e. the degree of climate-related impacts varied among regions). Currently, there is an urgent need for effective responses and adaptations to different agricultural districts and agricultural production modes. Therefore, the aim was to examine ecotones and explore trends and influential factors associated with grain production potential change. Using the Global Agro-ecological Zone model, the grain production potential of West Jilin, China under different conditions during various years were estimated, considering meteorological, soil, topographic, land use and other data. The results showed that total grain production potential (TGrPP) of West Jilin increased continuously from 1976 to 2013. The average annual increase in TGrPP was higher in period 1 (1976–2000) than period 2 (2000–2013). In period 1, grain production potential was influenced mainly by irrigation percentage changes, followed by land use change. The conversion of grassland to farmland was the most important land use change factor that was associated with increased grain production potential. Climate change affected grain production potential in period 1 negatively. In period 2, climate change had the largest impact and land use imparted the smallest effect on grain production potential. Finally, the decrease in irrigation percentage resulted in reduced grain production potential.